2016
DOI: 10.1126/scitranslmed.aag1767
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in CSF sTREM2 in dominantly inherited Alzheimer’s disease occur after amyloid deposition and neuronal injury

Abstract: Emerging evidence supports a role for innate immunity and microglia in Alzheimer’s disease (AD) pathophysiology. However, no marker related to microglia has been included in the temporal evolution models of AD. TREM2 is a transmembrane protein involved in innate immunity and is selectively expressed by microglia and genetically linked to AD and other neurodegenerative disorders. Its ectodomain is released by proteolysis as a soluble variant (sTREM2) and can be detected in the cerebrospinal fluid (CSF). In pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
256
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(290 citation statements)
references
References 69 publications
(115 reference statements)
32
256
2
Order By: Relevance
“…Therefore, although TREM2 may not have a dramatic effect on the overall Aβ content of the diseased brain, it strongly affects the ability of microglia to respond to and contain the plaques. In support of a role for TREM2 in microgliosis, a recent study found that production of sTREM2 is increased prior to the onset of symptoms but after initial markers of Aβ accumulation and neuronal injury [48]. This sTREM2 continues to increase until after the onset of symptoms and highlights the role for TREM2 in microgliosis at a critical point for the response to accumulating damage from disease.…”
Section: Trem2 In Diseasementioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, although TREM2 may not have a dramatic effect on the overall Aβ content of the diseased brain, it strongly affects the ability of microglia to respond to and contain the plaques. In support of a role for TREM2 in microgliosis, a recent study found that production of sTREM2 is increased prior to the onset of symptoms but after initial markers of Aβ accumulation and neuronal injury [48]. This sTREM2 continues to increase until after the onset of symptoms and highlights the role for TREM2 in microgliosis at a critical point for the response to accumulating damage from disease.…”
Section: Trem2 In Diseasementioning
confidence: 92%
“…While potential functions for sTREM2 are discussed below, it is notable that several studies have reported a correlation between CSF tau/p-tau levels and sTREM2 [29, 48, 5254]. Interestingly, in these studies, sTREM2 is more strongly correlated with CSF tau than Aβ.…”
Section: Trem2 In Diseasementioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, studies of subjects with dominantly inherited AD have shown that CSF TREM2 elevation can occur approximately 5 years before onset of symptoms and after [ 5 6 5 _ T D $ D I F F ] an increase in Ab deposition and CSF tau levels [114]. The effect of TREM2 genetic variants on CSF sTREM2 [ 5 6 6 _ T D $ D I F F ] do not show a consistent trend; for instance, one report suggests that the R47H variant can increase sTREM2, the T96K[ 5 6 7 _ T D $ D I F F ] /L211P/W191X (these variants were in linkage disequilibrium) variants slightly reduce, while the R62H variant does not seem to change sTREM2 levels compared to wild-type TREM2 carriers [109].…”
Section: Regulation Of Trem2 Gene Expressionmentioning
confidence: 99%